3D MoS2–Graphene Microspheres Consisting of Multiple Nanospheres with Superior Sodium Ion Storage Properties. (3rd February 2015) - Choi, Seung Ho; Ko, You Na; Lee, Jung‐Kul; Kang, Yun Chan
Abstract : A novel anode material for sodium‐ion batteries consisting of 3D graphene microspheres divided into several tens of uniform nanospheres coated with few‐layered MoS2 by a one‐pot spray pyrolysis process is prepared. The first discharge/charge capacities of the composite microspheres are 797 and 573 mA h g −1 at a current density of 0.2 A g −1 . The 600th discharge capacity of the composite microspheres at a current density of 1.5 A g −1 is 322 mA h g −1 . The Coulombic efficiency during the 600 cycles is as high as 99.98%. The outstanding Na ion storage properties of the 3D MoS2 –graphene composite microspheres may be attributed to the reduced stacking of the MoS2 layers and to the 3D structure of the porous graphene microspheres. The reduced stacking of the MoS2 layers relaxes the strain and lowers the barrier for Na + insertion. The empty nanospheres of the graphene offer voids for volume expansion and pathways for fast electron transfer during repeated cycling. Abstract : 3D MoS2 –graphene composite microspheres consisting of multiple nanospheres are prepared by a one‐pot spray pyrolysis process with high scale‐up potential. The 3D MoS2 –graphene composite microspheres show high reversible capacity and long cycle stability as anode materials for sodium‐ion batteries. The facile and continuous synthesis of 3D graphene‐based composite microspheres could be applied to the potential materials for various fields including energy storage.